ANALISIS TINDAK TUTUR GURU DAN SISWA DALAM PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH MENENGAH ATAS - Ari Rahma Nur Fitriana; Ani Rakhmawati; Budi Waluyo (Universitas Sebelas Maret, 2020)
The aims of this research are to describe and analyze: (1) the types of speech act between students and teachers dialogue in the Indonesian language learning situation at SMA Negeri 1 Karanganyar, and (2) the influence factors of speech act between students and teachers dialogue in Indonesian language learning at SMA Negeri 1 Karanganyar. This research is belong to a qualitative desciptive research which was conducted from June 2017 to December 2018. The primary data’s source in this research is the informan such as students and Indonesian language’s teachers, and also the speech act between them at Indonesian language’s learning . This research uses purposive sampling technique. Data validity uses a source’s and theori’s triangulation, while the data analysis using an interactive model that includes data collection, data reduction, data presentation, and conclusion. Based on the results of data analysis, the speech act which often used is illocusion with 37,5 % of percentage, locusion 73 %, and perlocusion 27,5 %. The speech act’s factors between teachers and students in Indonesian learning are the participants, the aim of speech act, the situation, context, which path, media, and the event of speech act.